A incorporação da saúde bucal no Programa Saúde da Família do Rio Grande do Norte: investigando a possibilidade de conversão do modelo assistencial - Souza, Tatyana Maria Silva de (2005)
The Health Family Program (HFP) was founded in the 1990s with the objective of changing the health care model through a restructuring of primary care. Oral health was officially incorporated into HFP mainly through the efforts of dental professionals, and was seen as a way to break from oral health care models based on curative, technical biological and inequity methods. Despite the fast expansion of HFP oral health teams, it is essential to ask if changes are really occurring in the oral health model of municipalities. Therefore, the purpose of this study is to evaluate the incorporation of oral health teams into the Health Family Program by analyzing the factors that may interfere positively or negatively in the implementation of this strategy and consequently in the process of changing oral health care models in the National Health System in the state of Rio Grande do Norte, Brazil. This evaluation involves three dimensions: access, work organization and strategies of planning. For this purpose,19 municipalities, geographically distributed according to Regional Public Health Units (RPHU), were randomly selected. The data collection instruments used were: structured interview of supervisors and dentists, structured observation, documental research and data from national health data banks. It was possible to identify critical points that may be impeding the implementation of oral health into HFP, such as, low incomes, no legal employment contract, difficulty in referring patients for high-complexity procedures, in developing intersectoral actions and program strategies such as epidemiologic diagnosis and evaluation of the new actions. The majority of municipalities showed little or no improvement in oral health care after incorporating the new model into HFP. All of them had failures in most of the aspects mentioned above. Furthermore, these municipalities are similar in other areas, such as low educational levels in children from 7 to 14 years of age, high child mortality rates and wide social inequalities. On the other hand, the five municipalities that had improved oral health, according to the categories analyzed, offered better living conditions to the population, with higher life expectancy, low infant mortality rates, per capita income among the highest in the state as well as high Human Development Index (HDI) means. Therefore, it is possible to conclude that public policies that include aspects beyond the health sector are decisive for a real change in health care models